Mohs Micrographic Surgery and Improved Survival in Skin Cancer: A Narrative Review - Pablo Balado-Simó; Miguel Mansilla-Polo; Daniel Morgado-Carrasco (Dermatology and Therapy)
Abstract Mohs micrographic surgery (MMS) has been shown to achieve very low recurrence rates in skin cancer, and some studies suggest it may improve survival. We conducted a narrative review to assess the impact of MMS on the survival of patients with various skin cancer subtypes. Some retrospective studies suggest that MMS may enhance survival in patients with head and neck melanoma, lentigo maligna, lentigo maligna melanoma, invasive cutaneous squamous cell carcinoma (cSCC) (especially high-risk cSCC), and high-risk dermatofibrosarcoma protuberans, and, possibly, with certain malignant adnexal tumors as well. It is crucial to take these findings into account so as to appropriately prioritize patients and ensure accessibility of MMS. In both Merkel cell carcinoma and leiomyosarcoma, MMS has not consistently demonstrated improved survival compared with wide excision. Evidence regarding improved survival in extramammary Paget’s disease remains limited.